Knowledge Level of Silkworm Rearers of Jammu Division of Jammu and Kashmir State - Ali, Lyaqet; Kher, S. K .; Slathia, P. S.; Bali, R.K.; Kumar, Manish; Bakshi, P. (Indian Journal of Extension Education, 2016)
The present study was carried out to know the knowledge level of silkworm rearers of Jammu division. The study revealed  that from three districts 60.00 per cent of respondents had medium knowledge followed by 32.92 per cent respondents had  low knowledge and 15.36 per cent respondents had high knowledge respectively. The overall mean knowledge score was  15.36 (+ 2.29). Majority of respondents (93.33%) had knowledge of time of pruning, (82.91%) of respondents had  knowledge of insects of mulberry plants,(90.41%) and (83.75%) had knowledge of methods of disinfecting the silkworm  body and rearing seat and disinfectants used for rearing room and appliances, (95.41%), (82.91%) and (78.75%) had  knowledge of control of insect/pest of silkworm, management of diseases, insect pest of silkworm and important diseases  of silkworms, (88.75%) and (83.26%) had knowledge of late age silkworm rearing techniques and low cost devices for  cocoon stifling, low percentage of respondents had knowledge of length and thickness of mulberry cuttings for  propagation and only (27.08%) respondents had knowledge of improved variety of mulberry, Less percentage of  respondents had knowledge of method of silkworm incubation, temperature cum humidity requirement for young as well  as late age rearing.
Keywords: Knowledge level; silkworm rearers